PENGEMBANGAN MEDIA AJAR INTERAKTIF BERBASIS WEB PADA MATERI DIGITASI PETA MATA KULIAH SISTEM INFORMASI GEOGRAFIS - Riansyah Putra; Sutrisno Sutrisno; Naufal Tinov Naufal Tinov (Jurnal Muara Pendidikan, 2025)
The advancement of digital technology in education necessitates the development of innovative, interactive, and adaptive learning media. This study aims to develop an interactive web-based learning medium designed to enhance students’ technical skills in the Map Digitization topic of the Geographic Information Systems course through the integration of interactive features. The research employed a Research and Development (R&D) method using the Richey and Klein model, which includes the stages of Design, Production, and Evaluation. The participants consisted of 31 students from the Building Construction Education Study Program who were directly involved in learning activities on the Map Digitization material. The data were analyzed using a quantitative descriptive approach to interpret the improvement in students’ learning performance. Based on the research findings, the developed web-based interactive learning media was declared highly valid by expert validators, with a validity percentage of 89% from material experts, 90% from media experts, and 94% from user feasibility assessments. These results indicate that the developed media meets the criteria of content accuracy, visual design quality, and interactivity, demonstrating its feasibility and effectiveness for use in the learning process of Map Digitization within the Geographic Information Systems course.